Bone Morphogenetic Protein Coating on Titanium Implant Surface: a Systematic Review - Haimov, Haim (J Oral Maxillofac Res, 2017)
OBJECTIVES: The purpose of the study is to systematically review the osseointegration process improvement by bone morphogenetic protein coating on titanium implant surface. MATERIAL AND METHODS: An electronic literature search was conducted through the MEDLINE (PubMed) and EMBASE databases. The search was restricted for articles published during the last 10 years from October 2006 to September 2016 and articles were limited to English language. RESULTS: A total of 41 articles were reviewed, and 8 of the most relevant articles that are suitable to the criteria were selected. Articles were analysed regarding concentration of bone morphogenetic protein (BMP), delivery systems, adverse reactions and the influence of the BMP on the bone and peri-implant surface in vivo. Finally, the present data included 340 implants and 236 models. CONCLUSIONS: It’s clearly shown from most of the examined studies that bone morphogenetic protein increases bone regeneration. Further studies should be done in order to induce and sustain bone formation activity. Osteogenic agent should be gradually liberated and not rapidly released with priority to three-dimension reservoir (incorporated) titanium implant surface in order to avoid following severe side effects: inflammation, bleeding, haematoma, oedema, erythema, and graft failure.